Philosophy as a Vocation and Personal Commitment: the Young Heidegger and the Question of Philosophy. - Garrido Periñán, Juan José (Problems / Problemos, 2021)
Determining what philosophy is for the young Heidegger is a complex task. It is also an ambiguous task in that it is considered unresolved and intricate due to its subsidiary link to factical life. This paper will try to show that from the approach of worried concern and from a critique of the theoretical attitude and worldviews, Heidegger conceives that philosophizing is committing oneself to the possibility of carrying out a personal transformation lived as a commitment of a personal nature. From this situation, which will be critically scrutinized in the development of the present paper, I will determine philosophy to be the setting in motion of the self-enlightenment of the life of each existent.